ACHIEVEMENT MOTIVATION IN RELATION TO FAMILY ENVIRONMENT AND GENDER - Mahajan, Monica (ShodhKosh: Journal of Visual and Performing Arts, 2022)
This study examines the relationship between achievement motivation, family environment, and gender among Class XI students. A total of 200 students from five schools in Hoshiarpur District were selected through multistage random sampling at both the school and section levels. The research employed the product moment correlation method and the t-test for statistical analysis. Results indicated a significant positive correlation between achievement motivation and various dimensions of the family environment, including Competitive Framework (Cf), Cohesion (Co), Expressiveness (Ex), Independence (In), Moral Orientation (Mo), Organization (Or), and Recreational Orientation (Ro). However, no significant gender-based differences in achievement motivation were observed. These findings underscore the importance of the family environment in fostering achievement motivation, while also suggesting that gender may not be a significant determinant in this context.